2020
DOI: 10.3389/fonc.2020.586580
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in Osteosarcoma Immune Microenvironment: Implications for Immunotherapy

Abstract: Osteosarcoma is a malignant primary bone tumor commonly occurring in children and adolescents. The treatment of local osteosarcoma is mainly based on surgical resection and chemotherapy, whereas the improvement of overall survival remains stagnant, especially in recurrent or metastatic cases. Tumor microenvironment (TME) is closely related to the occurrence and development of tumors, and macrophages are among the most abundant immune cells in the TME. Due to their vital roles in tumor progression, macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 143 publications
(206 reference statements)
1
43
0
Order By: Relevance
“… 29 A higher proportion of M2 macrophages is associated with a poorer prognosis, while the M1 population can enhance tumor-killing effects. 30 , 31 We observed a significant increase in M1 macrophages in the tumors from Akk -EVs-treated mice (representative image in Figure 3C and statistical analysis in Figure 3D : P = 0.0155), as well as a decrease in M2 macrophages ( P = 0.0318; Figure 3E ), while the proportion of an intermediate state of macrophages (expressing both MHC-II and CD206) remained unchanged ( P = 0.4425; Figure 3F ). We also examined the populations of macrophages in the peripheral blood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 A higher proportion of M2 macrophages is associated with a poorer prognosis, while the M1 population can enhance tumor-killing effects. 30 , 31 We observed a significant increase in M1 macrophages in the tumors from Akk -EVs-treated mice (representative image in Figure 3C and statistical analysis in Figure 3D : P = 0.0155), as well as a decrease in M2 macrophages ( P = 0.0318; Figure 3E ), while the proportion of an intermediate state of macrophages (expressing both MHC-II and CD206) remained unchanged ( P = 0.4425; Figure 3F ). We also examined the populations of macrophages in the peripheral blood.…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 11 , 50 Macrophages are highly plastic and heterogeneous cells, and the M1 and M2 phenotypes represent the two distinct termini of the macrophage activation spectrum. 31 , 51 Generally, M1 macrophages have tumoricidal activity by producing inflammatory cytokines and activating the immune response. 52 , 53 On the other hand, local signals in the TME activate M2 macrophages to trigger tumor neovascularization, immunosuppression, and tumor extracellular matrix reorganization, contributing to PCa progression.…”
Section: Discussionmentioning
confidence: 99%
“…In tumor microenvironment, tumor infiltrating immune cells account for the primary non-tumor constituents, which have been demonstrated to play an important role in prognostic prediction of OS patients (Zhang et al, 2020). Thus, TIME takes crucial significance in the development and progression of tumor, and accumulated evidence revealed that TIME was closely associated with pathogenesis of osteosarcoma (Heymann et al, 2019;Luo et al, 2020). Assessing the TIME of osteosarcoma helps to understand the immune status of tumor cells, is conducive to promote the development of immunotherapy and improve the prognosis of osteosarcoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage M1 contributes to tumor elimination and M2 serves as a promoter in tumorigenesis. Contrary to the cancer-promoting role of macrophages in a wide range of cancers, the high density of macrophages indicates longer survival in osteosarcoma [13]. However, there is a lack of systematic analysis of the heterogeneity of infiltrating immune cells in metastatic osteosarcoma.…”
Section: Introductionmentioning
confidence: 97%
“…Several reports have indicated that infiltrating immune cells were positively correlated with better clinical survival [9,10]. While Chen et al and Koirala et al have reported the opposite conclusion that the infiltrating immune cells act as a risk factor for osteosarcoma [11,12], M1 and M2 phenotypes were two polarized terminals of the macrophages that exhibit opposite functions in antitumor response [13]. Macrophage M1 contributes to tumor elimination and M2 serves as a promoter in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%